Performance enhanced high-nickel lithium metal batteries through stable cathode and anode electrolyte interfaces. Issue 6 (7th April 2020) - Liu, Yang; Wang, Mingshan; Chen, Junchen; Yang, Jun; Wang, Kai; Ren, Zhouhong; Xi, Wei; Huang, Yun; Zheng, Jianming; Li, Xing
Abstract : LMBs using an FEC optimized dual-salt electrolyte present excellent electrochemical performances because it could form a stable CEI and robust SEI. Abstract : The interface stability between the cathode and anode with the electrolyte is the key to the performances of lithium metal batteries (LMBs). An FEC optimized LiTFSI-LiBOB dual salt (Dual-salt + FEC) electrolyte is employed to systematically investigate its effects on LMBs. The high nickel Li‖NCM full LMBs using the Dual-salt + FEC electrolyte present significantly enhanced long-term cycling stability with 83.8% capacity retention after 500 cycles, which is much higher than 65.4% for the LiPF6 -based electrolyte. The improvement mechanism has been studied using aberration-corrected high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) imaging combined with X-ray photoelectron spectroscopy (XPS) and electrochemical impedance spectroscopy (EIS). The HAADF-STEM results firstly provide direct evidence at the atomic scale that the corrosion and transition metal dissolution for the high nickel NCM cathode cycled in the Dual-salt + FEC electrolyte could be effectively suppressed. Moreover, the HRTEM and XPS results further disclose that a stable CEI on the cathode and a thinner, smoother and strong adhesion of the SEI on the Li metal anode in the high nickel Li‖NCM cell could be achieved using the Dual-salt + FEC electrolyte. This holistic analysis of the cathode and anode electrolyte interfaces will significantly advance the LMB design principles through manipulation of the electrolyte chemistry.